The psychosocial burden of hidradenitis suppurativa in SingaporeCapsule Summary - Xue Ting Ooi, MRCP (UK); Ellie Choi, MRCP (UK); Huirong Han, MBBS; Hafizah Ahmad, BSc Biomedical Science (NUS); Kalyani Rajesh Patwardhan, MRCP, DDV, MD, MBBS; Nisha Suyien Chandran, MRCP (UK) (Elsevier, 2023)
Background: Hidradenitis suppurativa (HS) is a chronic debilitating inflammatory skin disorder known to result in significant psychological symptoms and impaired quality of life. However, most of these studies are limited to western countries, with limited data from other sociocultural regions. Objective: To understand the psychosocial burden of HS in the Asian context, by exploring the correlation between objective disease measures with psychosocial health and work productivity. Methods: A prospective single-center questionnaire study was conducted. A total of 45 patients with HS completed a questionnaire and examination by a dermatologist. Results: Higher objective disease severity scores (Hurley, physician global assessment, International Hidradenitis Suppurative Severity, and modified Sartorius) correlated with poorer quality of life (Dermatology Life Quality Index and Patient Global Assessment), increased anxiety and depression (hospital anxiety and depression scale) and at-work productivity loss. There was no significant correlation between objective disease severity and other domains Work productivity and activity impairment score or self-esteem (Rosenburg Self-Esteem Scale). Limitations: The main limitation of our study is the small sample size, assessment at a single time point, and lack of control cohort. Conclusion: Our findings demonstrate the impact of HS on a patient's psychosocial well-being and emphasize the importance of treating patients from a holistic standpoint.